2000
DOI: 10.1128/jvi.74.2.1051-1056.2000
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of VP22 Spread in Tissue Culture

Abstract: We compare methods of detection of intercellular transport of the herpes simplex virus protein VP22 and of a green fluorescent protein (GFP)-VP22 fusion protein. Spread of both proteins was observed by immunofluorescence (IF) using organic fixatives. Spread of both proteins was also detected by IF after paraformaldehyde (PFA) fixation and detergent permeabilization, albeit at reduced levels. However, while spread of GFP-VP22 was observed by examining intrinsic GFP fluorescence after methanol fixation, little s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
1
4

Year Published

2000
2000
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 15 publications
7
48
1
4
Order By: Relevance
“…39 Others concluded that methanol fixation is merely mimicking VP22-mediated protein transport. 40 This is contradicted by a report only investigating the fixation procedures of VP22 chimaeric proteins 31 together with our present analysis on quantitating a significant enhancement of the suicide gene effect. Additionally, many studies are dealing with the GFP-VP22 fusion being the only transgene tested.…”
Section: Mh3924a Cells Seeded In 24-well Plates Were Transduced With contrasting
confidence: 99%
“…39 Others concluded that methanol fixation is merely mimicking VP22-mediated protein transport. 40 This is contradicted by a report only investigating the fixation procedures of VP22 chimaeric proteins 31 together with our present analysis on quantitating a significant enhancement of the suicide gene effect. Additionally, many studies are dealing with the GFP-VP22 fusion being the only transgene tested.…”
Section: Mh3924a Cells Seeded In 24-well Plates Were Transduced With contrasting
confidence: 99%
“…In previous studies it has been shown that a GFP-VP22 fusion protein retains the properties of the native VP22 in a recombinant HSV-1 virus, 5 and allowed the characterisation in detail of the subcellular localisation of VP22 1 and its intercellular transfer. [6][7][8][9] GFP-VP22 fusion protein has been found to retain the intercellular trafficking properties of VP22 in all the cell lines studied.…”
Section: Introductionmentioning
confidence: 90%
“…Plasmids pEGFP-VP22 was created by cloning into the BamHI site of pEGFP-C1 (Clontech, Palo Alto, CA, USA) a BglIIBamHI fragment from pUL49epB 7 and adding the BamHI-XbaI fragment from pINSHNES (both kind gifts from Dr P O'Hare, Marie Curie Research Institute, Oxted, UK) containing the hemaglutinin (HA) epitope. Deletion constructs fused to EGFP were created by the following strategy: pEGFP-VP22 was cleaved with ApaI and XbaI.…”
Section: Cytoskeleton Nuclear and Binding To Chromatin Intercellular mentioning
confidence: 99%
“…4,25,26 This phenomenon could lead to an artefactual VP22 nuclear homing 18 not observed with paraformaldehyde fixation. 25 Conversely, other reports showed that efficient transport can be observed with both fixation methods 5 and in living cells. 7 It is noteworthy that we were able to detect intercellular trafficking of VP22 and P27VP22 using paraformaldehyde (Figures 1 and 3; cytometry) and methanol fixation (Figures 1 and 3; immunofluorescence).…”
Section: Discussionmentioning
confidence: 99%
“…3 Furthermore, VP22 retains its trafficking ability when genetically fused to an effector protein like the green fluorescent protein (GFP). [3][4][5][6][7] Thus, linkage to VP22 has permitted to enhance the biological activity of several proteins such as the tumour suppressor p53 8,9 or the products of the suicide genes thymidine kinase 10,11 and cytosine deaminase. 12 It was also used to deliver functional Flp recombinase 13 and to carry SV40 large T antigen to induce cell cycle reentry in terminally differentiated muscle cells.…”
Section: Introductionmentioning
confidence: 99%